Civil society ethos? Attitude differences between civil society elites and the population in Sweden - Lee, Jayeon; Scaramuzzino, Roberto (Acta sociologica, 2025)
Previous studies have found that elites differ from the general population not only in terms of their demographic and social composition but also with respect to policy preferences and attitudes. When it comes to civil society organisations, the issue of representation and representativeness of top-level leadership is of particular relevance, since a small number of individuals are expected to act on behalf of groups and causes that are not well acknowledged or even suppressed by other societal actors. Using two survey studies, this study compares the demographic composition and attitudes of the top-level leaders of the most resourceful civil society organisations in Sweden with those of the general population. We find that civil society elites are not demographically representative of the general population and that they also differ in attitudes when it comes to levels of trust, political orientations, satisfaction with democracy, and acceptance of income inequality. What is more interesting, however, is that the differences in attitudes cannot be fully explained by the skewed demographic characteristics of the civil society leaders, indicating that there might be distinctive sets of values and attitudes underpinning a ‘civil society ethos’.